Improving the iron grade of indigenous laterite ore through gravity and magnetic separation - Muhammad Raheel Bawani; Waqas Anjum; Sikander Almani; Ali Hassan; Ramez Raja; Noor Muhammad Lashari (Mehran University Research Journal of Engineering and Technology)
The depletion of high-grade iron ore reserves has increased the need to process low-grade iron ores efficiently. This study focused on improving the iron grade of indigenous laterite ore located at Jhimpir (Thatta district), using gravity and magnetic separation techniques. Mineralogical analysis confirms the presence of goethite, hematite, quartz, calcite, and clay minerals. SEM-EDS mapping shows that silicon (Si) and aluminum (Al) are scattered on the surface of iron-bearing minerals. The stereomicroscopic images showed that the particles below 600 microns are well liberated, but aluminosilicate impurities remain finely interlocked into the iron-bearing minerals. Gravity separation increases the iron content to 53% with a recovery of 35%, while magnetic separation improves the iron content to 58% but with a lower recovery of 25%. The iron content improves further when both methods are used together, but the overall recovery remains low (less than 35%) due to fine impurities within the iron-bearing minerals. These methods are ideal for preliminary concentration, where the goal is to reject coarse gangue and achieve moderate enrichment before using more expensive flotation methods. This research provides valuable insights into optimizing beneficiation methods for the laterite ore. The findings can help develop efficient processes to upgrade low-grade iron ore, making it more suitable for industrial use.